Nominal and pronominal negative concord, through the lens of Belizean and Jamaican Creole - van der Auwera Johan (Linguistics, 2022)
The article aims to advance the general understanding of negative concord through a comparative analysis of nominal and pronominal negative concord in Jamaican and Belizean Creole, based on the translations of the New Testament. It supplies a general characterization of Jamaican and Belizean negative concord and then focuses on negative concord with a negator like what corresponds to English not and either a pronoun or a nominal like what corresponds to English nobody or no man, respectively. The paper makes a strong plea for studying nominal negative concord in its own right. It shows how it differs from pronominal negative concord and for both it lays bare a variety of non-concordant patterns. It explains the variation in terms of a number of principles, one of which is what is standardly called the ‘Negative First’ principle, but it is defined in a new way. The article shows that there can be concord with definite negative nominals.